Effectiveness of ECMO for burn-related acute respiratory distress syndrome. Issue 2 (March 2019) - Eldredge, R.Scott; Zhai, Yan; Cochran, Amalia
Highlights: ECMO was utilized for burn patients with severe ARDS. Appropriate patient selection and early decision for ECMO result in high rates of survival for burn patients with severe ARDS. ECMO provides an option for salvage in burn patients with severe ARDS. Abstract: Introduction: Acute respiratory distress syndrome (ARDS) is a complication that affects approximately 40% of burn patients and is associated with high mortality rates. Extracorporeal membrane oxygenation (ECMO) therapy is a management option for severe refractory hypoxemic respiratory failure; however, there is little literature reporting the effectiveness of this therapy in burns. Our study objective was to review patient outcomes in burns following severe ARDS treated with ECMO. Methods: We retrospectively reviewed all patients treated with ECMO for ARDS who received their burn care at a single regional burn center between 9/1/2006 and 8/31/2016. Primary patient outcome examined was discharge disposition. Results: We identified 8 patients who had ARDS secondary to burn who were placed onto ECMO during this 10-year period. The average APACHE score, SOFA score, and P/F ratio were 21 ± 3, 9 ± 2, and 59 ± 8, respectively, at the time of decision for ECMO. No ECMO-related complications were identified. Out of the 8 patients reviewed, 1 died, 4 were discharged to acute rehabilitation or a long-term acute care facility, and 3 were discharged to home. Conclusion: Mortality in burn patients with ARDS who are managed with ECMO is extremely low. Careful selection and timely intervention with ECMO contributed to good clinical outcomes.